2021
DOI: 10.1186/s12890-021-01636-x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating activated immune cells as a potential blood biomarkers of non-small cell lung cancer occurrence and progression

Abstract: Background Treatment for non-small cell lung cancer (NSCLC) has greatly improved in recent years. However, noninvasive early screening for carcinogenesis and progression unclear. The aim of this study was to explore the predictive value of peripheral blood immune cells in untreated NSCLC patients. Methods We retrospectively enrolled 305 untreated NSCLC patients and 132 healthy participants from February 2016 to August 2019 in Peking Union Medical C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Lv and colleagues compared the NLR between node-positive and node-negative patients but no difference was found [ 26 ]. Nevertheless, in the present study, we found NLR and PLR were both significantly higher in pN+ patients, consistent with the results of Chen and Wang [ 18 , 19 ]. This may be mainly due to the higher proportion of N2 stage cases among patients presented with lymph nodes metastasis in our cohort.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lv and colleagues compared the NLR between node-positive and node-negative patients but no difference was found [ 26 ]. Nevertheless, in the present study, we found NLR and PLR were both significantly higher in pN+ patients, consistent with the results of Chen and Wang [ 18 , 19 ]. This may be mainly due to the higher proportion of N2 stage cases among patients presented with lymph nodes metastasis in our cohort.…”
Section: Discussionsupporting
confidence: 93%
“…Elevated NLR and PLR usually indicate higher invasion of the tumor. A significant difference was seen in the two parameters between patients with different N stages [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we speculate that combined parameters based on lymphocytes may be crucial for achieving a better response to cancer therapy. The absolute neutrophil count has been positively associated with advanced cancer stage in some studies ( 22 , 23 ), consistent with our results. Neutrophils are commonly represented as a reflection of tumor burden because of their contribution to tumor-related inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…A series of recent studies identified multiple immune cell subsets captured in peripheral blood instead of the TME that supports systemic immune responses in immunotherapy monitoring for different tumor types. For example, CD8 + CD28 + T cells were reported as an independent predictive biomarker for non-invasive early screening in NSCLC occurrence and progression ( 29 ). When compared with healthy volunteers, a decrease in the CD3 + TCRγδ + lymphocyte subset was observed in multiple myeloma patients ( 30 ).…”
Section: Discussionmentioning
confidence: 99%